Bitterroot : a novel - Vitello, Suzy, 1961- (Sibylline Press, 2024)
Set in the fictional town of Steeplejack, nestled in the Bitterroot Mountains, Hazel Mackenzie provides law enforcement with sketch art and victim reconstruction following suspected crimes. Hazel is catapulted from observer to participant when her husband dies in an accident and then soon after, her gay twin brother Kento is shot by a member of Steeplejack's growing anti-LGBTQ community during a gender reveal party for his child. Hazel soon discovers her husband wasn't who she thought he was. She uncovers hidden family secrets about her grandparents' forced internment during World War II, mirroring the same racism and prejudice that threaten to strip Kento and his husband of their basic rights to their baby. As physical violence charges up her driveway and engulfs her life, Hazel battles for herself, her brother, and a town torn apart by hate. And somehow during all of this, she stumbles on a different kind of love and a more courageous way to live her life.